Managing the water and wastewater utility - Dolan, Roger J. (Water Environment Federation, 2003)
Learn from the Masters of Public Utility Management! Roger J. Dolan P.E., DEE, T. Duncan Rose, Robert A. Baker, P.E., and Michael J. Barnes, P.E., encourage young water quality professionals to embark upon a career of challenges and responsibilities in utility management. These experts, speaking from on-the-job experience, stress the importance of leadership and management skills, and the core understanding of the utility business. This book is designed to help transform the specialist into a leader, and is the ideal textbook for the student or young professional studying to become a utility manager.
Keywords: Water utilities -- United States -- Management.; Water-supply -- United States -- Management.; Water treatment plants -- United States -- Management.; Sewage disposal plants -- United States -- Management.; elektronické knihy; electronic books